Effects of environmental conditions and catch processing on survival probability of plaice discards in the North Sea pulse trawl fishery. - Edward Schram; Pieke Molenaar; Paul W Goedhart; Jan Jaap Poos (PLoS ONE, 2023)
Undersized European plaice dominate the discarded fraction of the catch of the beam trawl fisheries for sole in the Southern North Sea. Effects of environmental conditions at sea and of the use of a water-filled hopper on the survival of undersized European plaice discarded by pulse trawl fisheries were explored. During trips with commercial pulse-trawlers catches were discharged in either water-filled hoppers or conventional dry hoppers. For both hoppers, undersized plaice were sampled from the sorting belt. After assessment of vitality status, sampled fish were housed in dedicated survival monitoring tanks on board. Upon return in the harbour fish were transferred to the laboratory to monitor their survival for up to 18 days post-catch. Conditions at sea, such as wave height and water temperature, as prevailing during these trips were recorded or obtained from public data sources. The overall estimate for the survival probability for plaice discarded by pulse trawl fisheries is 12% (95% CI: 8% - 18%). Both water temperature and vitality status had strong effects on survival probabilities of discarded plaice. Increasing water temperature increased mortality. The vitality of the fish could be moderately increased by using a water-filled hopper to collect the fish on deck, but we found no significant direct effect of hopper type on plaice discard survival. It seems that to increase discards survival, fish need to be landed on deck in much better condition by a reduction of the impact of capture and hauling processes on fish condition.